Relationship of the Brussels I Regulation vis-à-vis Legal Remedies Provided by National Enforcement Laws - Orož, Damjan (LeXonomica, 2018)
Article discuss the impact of the Brussels I and Brussels I bis Regulations on Slovenian enforcement proceedings. The aim of the Brussels I bis Regulation is to ensure creditors a simpler but mostly quicker access to enforcement in case a judgment must be enforced in a state other than the Member State of origin. The new regulatory framework will certainly facilitate quicker access to enforcement for creditors. However, this can only be ensured categorically in the first phase of enforcement, i.e. the seizure of assets (distraint). In subsequent enforcement phases successful enforcement in favour of the creditor could be stayed if the debtor decides to enforce grounds used to challenge the enforceability of a foreign judgment. A major distinction is that the control of enforceability will only proceed if and when the debtor so requests. Razmerje med Uredbo Bruselj I in pravnimi sredstvi, ki jih predvidevajo nacionalne ureditve izvršilnega prava Prispevek obravnava vpliv Uredb BU I in BU I bis na slovenski izvršilni postopek. Namen BU I bis je upniku zagotoviti lažji, predvsem pa hitrejši dostop do izvršbe v primeru, da je treba sodbo izvršiti v drugi državi kot v državi izvora. Gotovo bo nova ureditev upniku zagotovila hitrejši dostop do izvršbe, vendar to lahko kategorično zagotovimo le za prvo fazo izvršbe, to je rubež premoženja. V kasnejših fazah izvršitve pa se utegne upniku uspešna izvršba odložiti, če se dolžnik odloči uveljavljati razloge, s katerimi bo nasprotoval izvršljivosti tuje sodne odločbe. Pomembna razlika je ta, da se bo kontrola izvršljivosti opravila le ko in če bo dolžnik to zahteval.